The Historical Overview of the Hungarian Police - Sallai, János (Magyar Rendészet, 2016)
The dawn of the Hungarian police and the forces of law and order dates back to the second half of the 19th century. The first prominent Hungarian practitioner of the Police Science was Agoston Karvasy, a Hungarian jurist. This study presents the development of the Hungarian Police Science and the concept of policing from the 19th century to the present, when the Hungarian Accreditation Committee by the decision of the 2012/8/III/2/2. (2012th 09, 28) recognized Police Science as a scientific discipline. While reviewing the history of policing it can be observed how law enforcement changed with the modernization of Europe and Hungary and how it reached its present from. I find it interesting that researches and debates on enforcement laws are conducted mainly by scholars and professional of administrative law and only occasionally by practitioners with noticeable writings.